2021
DOI: 10.35882/jeeemi.v3i1.9
|View full text |Cite
|
Sign up to set email alerts
|

Design and Build A Photovoltaic and Vertical Savonious Turbine Power Plant as an Alternative Power Supply to Help Save Energy in Skyscrapers

Abstract: Indonesia is a tropical country, because its area that crosses the equator has enormous solar potential, with a radiation magnitude of 4.80 kWh / m2 / day / day or equivalent to 112,000 GWp. Meanwhile, the solar energy received by the earth is 1.74 x 1017 W / hour, of which about 1-2% is converted into wind energy. However, in terms of total energy potential, Indonesia only uses around 10 MWp of solar energy, the difference is that wind energy which is planned to reach 250 MW in 2025 only uses 1 MW of the tota… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
9

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 0 publications
0
3
0
9
Order By: Relevance
“…where Psys/A is the power produced per unit area of the blade in W/m 2 [13], [14], Cp is power coefficient, ηtr is transmission efficiency [15], ηb is battery efficiency [16], ηg is generator efficiency [17], ρ is air density in kg/m 3 [18], and v is wind speed in m/s. From the calculations, it is found that the maximum power that can be generated is 7.486 W/m 2 .…”
Section: Methods 21 Calculation Of Generated Power Potentialmentioning
confidence: 99%
“…where Psys/A is the power produced per unit area of the blade in W/m 2 [13], [14], Cp is power coefficient, ηtr is transmission efficiency [15], ηb is battery efficiency [16], ηg is generator efficiency [17], ρ is air density in kg/m 3 [18], and v is wind speed in m/s. From the calculations, it is found that the maximum power that can be generated is 7.486 W/m 2 .…”
Section: Methods 21 Calculation Of Generated Power Potentialmentioning
confidence: 99%
“…Beberapa bangunan yang membutuhkan banyak energi (terutama listrik) adalah gedung bertingkat, pabrik, rumah sakit, gedung perkantoran dan pusat perbelanjaan [4]. Gedung bertingkat merupakan industri yang termasuk kategori pusat perbelanjaan dan membutuhkan banyak listrik.…”
Section: Pendahuluanunclassified
“…Pendinginan adalah proses menurunkan suhu dan membuat suhu dalam ruangan atau bahan dalam ruangan lebih rendah dari suhu lingkungan. Dengan kata lain, ruang lingkup teknologi refrigerasi terletak pada proses pendinginan [8]. Teknologi refrigerasi tidak hanya dapat mendinginkan udara, tetapi juga membuat pengguna atau pemakainya merasa nyaman (comfortable communication).…”
Section: Refrigerasi Dan Pengkondisi Udaraunclassified
“…So from the research, researchers wanted to develop a buckboost converter voltage stabilizer on a solar power plant [12]. An advantage of this system is the voltage output of the buckboost converter that its value makes would remain on a set of points even if input from the renewable energy is fluctuating [13].…”
Section: Introductionmentioning
confidence: 99%